3D Laser Displays Based on Circularly Polarized Lasing from Cholesteric Liquid Crystal Arrays. Issue 37 (1st August 2021) - Zhan, Xiuqin; Xu, Fa‐Feng; Zhou, Zhonghao; Yan, Yongli; Yao, Jiannian; Zhao, Yong Sheng
Abstract: 3D laser displays play an important role in next‐generation display technologies owing to the ultimate visual experience they provide. Circularly polarized (CP) laser emissions, featuring optical rotatory power and invariability under rotations, are attractive for 3D displays due to potential in enhancing contrast ratio and comfortability. However, the lack of pixelated self‐emissive CP microlaser arrays as display panels hinders the implementation of 3D laser displays. Here, full‐color 3D laser displays are demonstrated based on CP lasing with inkjet‐printed cholesteric liquid crystal (CLC) arrays as display panels. Individual CP lasers are realized by embedding fluorescent dyes into CLCs with their left‐/right‐handed helical superstructures serving as distributed feedback microcavities, bringing in ultrahigh circular polarization degree values ( g em  = 1.6). These CP microlaser pixels exhibit excellent far‐field color‐rendering features and a relatively large color gamut for high‐fidelity displays. With these printed CLC red–green–blue (RGB) microlaser arrays serving as display panels, proof‐of‐concept full‐color 3D laser displays are demonstrated via delivering images with orthogonal CP laser emissions into one's left and right eyes. These results provide valuable enlightenment for the development of 3D laser displays. Abstract : Full‐color 3D laser displays are demonstrated on cholesteric liquid crystal arrays, which comprise two sets of red–green–blue (RGB) pixels to present two images with orthogonal circularly polarized laser emissions. Stereoscopic images can be generated in a viewer's mind by fusing the two images acquired by the left and right eyes, respectively.